Simple phosphinate ligands access zinc clusters identified in the synthesis of zinc oxide nanoparticles - Sebastian D. Pike (Nature Portfolio, 2016)
Ligands and surfactants play an important part in the synthesis of nanoparticles from molecular precursors although their exact roles are poorly understood. Here, the authors isolate a range of intermediate sized zinc clusters and are able to spectroscopically probe the self-assembly and ligand effects.